A randomized double-blinded study assessing the dose-response of ropivacaine with dexmedetomidine for maintenance of labor with epidural analgesia in nulliparous parturients - Shen, Yao-Hua; Drzymalski, Dan M.; Zhu, Bin-Xiang; Lin, Su-Feng; Tu, Fang-Qin; Shen, Bei; Xiao, Fei (Frontiers in Pharmacology, 2023)
The combination of ropivacaine and dexmedetomidine has been used as an epidural analgesic for inducing labor. However, there is limited data regarding the administration of epidural analgesia for labor maintenance, hence, this study aimed to determine the optimum concentration through dose-response curves of ropivacaine plus dexmedetomidine, which could be used along with the Programmed Intermittent Epidural Bolus (PIEB) technique.Methods: One hundred parturients were randomized into 4 groups who were administered four different doses of ropivacaine (dexmedetomidine at 0.4 μg.mL -1 ): 0.04%, 0.06%, 0.08%, and 0.1%. The primary outcome that was determined included the proportion of patients experiencing breakthrough pain during their 1 st stage of labor. Breakthrough pain was described as a visual analog scale [VAS] score of >30 mm, requiring supplemental epidural analgesia after the administration of at least one patient-controlled bolus. The effective concentration of analgesia that was used for labor maintenance in 50% (EC50) and 90% (EC90) of patients were calculated with the help of probit regression. Secondary outcomes included epidural block characteristics, side effects, neonatal outcomes, and patient satisfaction.The results indicated that the proportion of patients without breakthrough pain was 45% (10/22), 55% (12/22), 67% (16/24), and 87% (20/23) for 0.04%, 0.06%, 0.08%, and 0.10% doses of the analgesic that were administered, respectively. The EC50 value was 0.051% (95% confidence interval [CI], 0.011-0.065%) while the EC90 value was recorded to be 0.117% (95% CI, 0.094-0.212%). Side effects were similar among groups.A ropivacaine dose of 0.117% can be used as epidural analgesia for maintaining the 1st stage of labor when it was combined with dexmedetomidine (0.4 μg.mL-1) and the PIEB technique.Trial registration: This study has been registered in the Chinese Clinical Trial Register (https://www.chictr.org.cn/index.aspx) identifier: ChiCTR2200059557